Easy-to-Read Book Material in Croatian Public Libraries - Petrović, Borna; Poje, Irena; Faletar, Sanjica (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2026)
The paper presents findings of a study that evaluated the inclusion of easy-to-read materials in Croatian public libraries. Using a checklist method, catalogues of the 41 largest and smallest public libraries in each Croatian county were compared with the Bibliography of Printed Easy-to-Read Materials Published in Croatia, comprising 29 titles. The collected data were analyzed descriptively using SPSS. Findings show that only one studied library holds all titles, and nearly half of them have more than half of the titles listed in the Bibliography. Although there are some deviations, the study identified the following pattern: an increasing number of titles and copies was observed relative to county population size and library type by service area. In most cases, the largest number of copies and titles is found in the largest libraries. As the study focused only on the largest and smallest county libraries, the results are not generalizable to all Croatian public libraries. The results highlight the strengths and weaknesses of the surveyed collections regarding their coverage of easy-to-read materials and offer guidance for librarians in future collection development of this material. Given that reading difficulties, especially dyslexia, are issues that can significantly impair one’s quality of life, public libraries have the opportunity, through the acquisition and promotion of easy-to-read materials, to substantially contribute to improving the quality of life for such individuals and to raise public awareness of these issues. This is the first research that investigated the inclusion of easy-to-read materials in the collections of public libraries in Croatia.